P27 Reduction in alanine aminotransferase values in diabetic patients receiving long-term oral antibiotics: does modulation of gut flora affect hepatic inflammation in non-alcoholic fatty liver disease?. (6th September 2011) - Leach, L; Cobbold, J F L; Valabhji, J; Thursz, M R
Abstract : Introduction: The gut microbiota may play a role in host metabolic processes and have been linked to the pathophysiology of non-alcoholic fatty liver disease (NAFLD). Murine studies have suggested beneficial effects of modulating the gut microbiota using antibiotics, however studies have not looked at the effect of long-term antibiotic therapy in humans. Aim: To investigate the effects of prolonged broad-spectrum antibiotics in patients attending the diabetic foot clinic who are likely to have NAFLD. It was hypothesised that long-term oral antibiotic administration would result in a decrease in serum alanine aminotransferase (ALT) values after 3 months compared to baseline. Method: 43 diabetic patients without known hepatic comorbidity, who had taken a minimum of 3 months' broad-spectrum oral antibiotics (predominantly co-amoxiclav) in the diabetic foot clinic were identified retrospectively. Demographic and clinical data were extracted from clinic letters, patient notes, and computer databases. The primary outcome measure was the change in ALT value at day 90 of antibiotics compared to day 0. Other outcome measures were a change in patient weight, glycosylated haemoglobin (HbA1c), white cell count, bilirubin and alkaline phosphatase at day 90 from day 0. The wilcoxon signed rank test was used for paired non-parametric data. Results: All patients with abnormal ALT at baseline (n=6) had a significant decrease in ALT from median 43 (41–48) U/l on day 0, to 32 (29–35) U/l on day 90 (p=0.03). 37 patients who had a normal ALT at baseline had a small but significant increase in ALT from median 17 (13–23) U/l on day 0, to 20 (14–28) U/l on day 90 (p=0.02). In the 20 patients with paired HbA1c values, there was a statistically significant decrease in HbA1c with antibiotic use (p=0.03). There were no significant associations in change in ALT at 90 days with weight change, white cell count, bilirubin, alkaline phosphatase, antibiotic regime or other medications. Conclusion: The robust decrease in ALT values in patients with abnormal baseline ALTs (and therefore likely to have NAFLD) provides indirect evidence that modulation of gut microbiota with oral antibiotics may reduce hepatic inflammation in NAFLD. The possibility of sepsis-induced liver damage accounting for the changes is countered by no change in white cell count, bilirubin or alkaline phosphatase, while reduction in HbA1c without weight change points to reduced insulin resistance. Prospective studies on patients with biopsy-proven non-alcoholic steatohepatitis are awaited.